Cryptic speciation in arid mountains: An integrative revision of the Pristurus rupestris species complex (Squamata, Sphaerodactylidae) from Arabia based on morphological, genetic and genomic data, with the description of four new species - Bernat Burriel-Carranza; Thore Koppetsch; Juliana Tabares; Adrián Talavera; Gabriel Mochales-Riaño; Maria Estarellas; Benjamin Wipfler; Johannes Els; Marc Simó-Riudalbas; Dean Adams; Saleh Al Saadi; Joan Garcia-Porta; et al. (PLoS ONE, 2025)
In the arid landscapes of the Arabian Peninsula, high levels of cryptic diversity among reptiles, and especially in geckos, have recently been revealed. Mountain ranges within the peninsula were shown to contain the highest richness of reptile endemicity, serving as refugia to species less adapted to the hyper-arid conditions of the lowlands. With up to 19 endemic reptile species, the Hajar Mountains of southeastern Arabia are a clear example of this pattern. Owing to its old geological history, complex topography and geographic isolation from the rest of the peninsula, this mountain range rises as a hotspot of reptile biodiversity and endemicity in Arabia, and provides the perfect scenario to study the processes of evolution and diversification of reptiles in arid mountain ranges. In the present study we investigate the systematics of the Pristurus rupestris species complex, a group of geckos exhibiting cryptic morphological traits along with a remarkably deep evolutionary history. Initially considered a single species distributed throughout coastal Arabia, and with some scattered populations at the Horn of Africa, several recent studies have shown that Pristurus rupestris actually comprises a species complex restricted to the Hajar Mountains of southeastern Arabia. Here, we utilize an integrative approach assembling several morphological, genetic, genomic, and ecological datasets to resolve this long-standing systematic challenge. Results support the existence of four new cryptic Pristurus species in the Hajar Mountains with three new Oman endemics. While no unique diagnostic morphological characters were identified, some slight morphological differences occur between species, especially among high-elevation species relative to the rest. Despite the lack of clear morphological differentiation, extreme levels of genetic variation were found between species with genetic distances of up to 24% in the 12S mitochondrial marker, resulting from deep divergence times of up to 10 mya. Moreover, all species have been found in sympatry with at least another representative of the species complex and without any signs of apparent and ongoing gene flow among them. These findings yield profound implications for conservation efforts, as one of these newly described species presents an extremely restricted distribution (only known from a single locality and three individuals), requiring immediate attention for protection. Overall, this study sheds light on the hidden diversity within the P. rupestris species complex, emphasizing the importance of preserving biodiversity in the face of ongoing environmental changes, while highlighting, once again, the Hajar Mountains of southeastern Arabia as a cradle of reptile biodiversity.